The Influence of Physical Work Environment and Compensation on Employee Productivity with Job Satisfaction as an Intervening Variable at PT. Indomarco Prismatama Medan Branch - Bu'ulolo, Melia; Wahyuni, Wira; Ahmad Karim; Rambe, Saima (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract Human resources (HR) play a crucial role in organizations, both in the public and private sectors. PT. Indomarco Prismatama Medan Branch has experienced a significant decline in employee attendance, decreasing by 2.2% from the first to the second quarter, 8.2% in the third quarter, and 3.2% in the fourth quarter. This study employs a quantitative approach with a sample of 60 employees. The t-test results indicate that physical work environment (X1) and compensation (X2) significantly influence work productivity (Y) and job satisfaction (Z), with t-values greater than t-table values and significance levels < 0.05. Additionally, job satisfaction (Z) also significantly affects work productivity (Y). The F-test results show that the work environment and compensation simultaneously influence work productivity, with F-value (33.129) > F-table (3.16). The analysis of direct and indirect effects reveals that the indirect effect (0.681) is greater than the direct effect (0.011883), indicating that job satisfaction acts as an intervening variable in the relationship between the physical work environment and compensation toward work productivity.